Evaluating the Effects of Soybean Meal Levels and Valine, Isoleucine, and Tryptophan Adjustment in Diets with or without Dried Distillers Grain Solubles on Finishing Pig Performance and Carcass Characteristics - Macie E. Reeb; Jason C. Woodworth; Joel M. DeRouchey; Mike D. Tokach; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 1,080 pigs (PIC 337 × 1050; initially 58.4 ± 1.26 lb) were used in this 121-d experiment to determine the effects of added soybean meal (SBM) versus using an amino acid (AA) adjustment in diets with dried distillers grains with solubles (DDGS) on growth performance and carcass characteristics. Pens were randomly assigned to 1 of 4 dietary treatments in a completely randomized design. There were 27 pigs per pen and 10 replications per treatment. Treatments diets consisted of: 1) a control diet containing high SBM with no DDGS; 2) DDGS-based diet with a medium level of SBM; 3) DDGS-based diet with low SBM + Val, Ile, and Trp to equal levels as in diet 2; and 4) Treatment 3 but without the Val, Ile, and Trp adjustment (still meeting requirement estimates for all AA). Overall, from d 0 to 83, pigs fed the DDGS-based diets had decreased ADG (P= 0.014) compared to pigs fed the control diet. There was an improvement (P<0.05) in feed efficiency for pigs fed the high SBM diet without DDGS as compared to pigs fed diets including DDGS and low levels of SBM with no AA adjustment, with the other two treatments intermediate. There was a tendency (P= 0.074) for a treatment difference in HCW between treatments. Pigs fed the high SBM diet without DDGS had increased HCW (P= 0.018) compared to pigs fed the three diets containing DDGS. There were no differences between treatments for percentage lean, loin depth, or backfat (P>0.10). In conclusion, pigs fed diets containing no DDGS and higher levels of SBM had improved growth performance and HCW compared with pigs fed DDGS-based diets. When feeding diets containing DDGS, pigs fed without the AA adjustment had poorer overall feed efficiency (P<0.05) than those fed the control diet with pigs fed the other two diets intermediate, showing the importance of the AA adjustment in maintaining performance.
Keywords: branch chain amino acids; dried distillers grains with solubles; soybean meal; finishing pigs